Preparation and characterization of a novel tetrakis(4-hydroxyphenyl)porphyrin–graphene oxide nanocomposite and application in an optical sensor and determination of mercury ions. Issue 113 (2nd November 2015) - Zare-Dorabei, Rouholah; Rahimi, Rahmatollah; Koohi, Asgar; Zargari, Solmaz
Abstract : Optical chemical sensor for determination of mercury ions. Abstract : In this work, for the first time we report a highly specific and sensitive mercury ion (Hg 2+ ) optical sensor (optode). The optode was prepared by recently synthesized nanocomposites, based on 5, 10, 15, 20-tetrakis(4-hydroxyphenyl)porphyrin (THPP) and graphene oxide nanosheets. In this nanocomposite, porphyrin was stabilized on the graphene oxide nanosheets. X-ray diffraction (XRD), UV-vis spectroscopy, field-emission scanning electron microscopy (FE-SEM) and FT-IR were employed to characterize the prepared nanocomposite. In the prepared optical chemical sensor, the formation of a Hg 2+ –ionophore complex between the mercury ions and the membrane phase, changes the UV-vis absorbance of the sensor. To improve the sensor response, various experimental parameters such as pH, concentration of THPP and graphene oxide nanosheets in the prepared nanocomposite were optimized. This optode exhibited a linear range of 6.0 × 10 −9 to 6.0 × 10 −5 mol L −1 Hg(ii ) with a detection limit of 3.2 × 10 −9 mol L −1 and a response time of ∼210 s. It manifests advantages of low detection limit, fast response time, wide dynamic range, good reversibility, high reproducibility and also remarkable selectivity regarding the number of transition metals ions ( i.e. Pb 2+, Cr 3+, Zn 2+, Cd 2+, Cu 2+, Fe 2+, and Ni 2+ ). This optode was applied for determining Hg(ii ) ions in water samples.